Large-Scale Automated Production of Highly Ordered Ultralong Hydroxyapatite Nanowires and Construction of Various Fire-Resistant Flexible Ordered Architectures - Chen, Feng; Zhu, Ying-Jie (ACS nano, 2016)
Practical applications of nanostructured materials have been largely limited by the difficulties in controllable and scaled-up synthesis, large-sized highly ordered self-assembly, and macroscopic processing of nanostructures. Hydroxyapatite (HAP), the major inorganic component of human bone and tooth, is an important biomaterial with high biocompatibility, bioactivity, and high thermal stability. Large-sized highly ordered HAP nanostructures are of great significance for applications in various fields and for understanding the formation mechanisms of bone and tooth. However, the synthesis of large-sized highly ordered HAP nanostructures remains a great challenge, especially for the preparation of large-sized highly ordered ultralong HAP nanowires because ultralong HAP nanowires are easily tangled and aggregated. Herein, we report our three main research findings: (1) the large-scale synthesis of highly flexible ultralong HAP nanowires with lengths up to >100 μm and aspect ratios up to >10000; (2) the demonstration of a strategy for the rapid automated production of highly flexible, fire-resistant, large-sized, self-assembled highly ordered ultralong HAP nanowires (SHOUHNs) at room temperature; and (3) the successful construction of various flexible fire-resistant HAP ordered architectures using the SHOUHNs, such as high-strength highly flexible nanostructured ropes (nanoropes), highly flexible textiles, and 3-D printed well-defined highly ordered patterns. The SHOUHNs are successively formed from the nanoscale to the microscale then to the macroscale, and the ordering direction of the ordered HAP structure is controllable. These ordered HAP architectures made from the SHOUHNs, such as highly flexible textiles, may be engineered into advanced functional products for applications in various fields, for example, fireproof clothing.